BENTURAN KEPENTINGAN TIDAK LANGSUNG OLEH DIREKTUR DALAM MENGELOLA PERSEROAN TERBATAS - Marsella, Marsella (Universitas Medan Area, 2016)
Birth of Law Number 40 Year 2007 regarding Limited Liability Company (hereinafterreferred to as the Company Law). is expected to provide a solution to the limited liabilitycompany as a legal entity to deal with the demands of economic development today.Demands faced limited liability company is about transactions conducted by the relevantorgans, in particular by the director of a limited liability company with others having aclose relationship with the director of a limited liability company that raises a conflict ofinterest. that actions such as self dealing, accepting gifts or benefits include all forms ofbribery and kick-back fee, peddling influence (influence pedding), utilizing companyassets for personal benefit (using employer's propety for private advantage) and takeadvantage of confidential information (using confidential information) is some form ofConflict of Interest. Factors that cause the Conflict of Interest is the internal factors arederived from transactions Conflict of Interest is done inside the company may for personalbenefit of its directors, while external factors are transactions Conflict of Interest made bythe director to gain own private not for profit company, but do it in silence -diam andcollusion. the arrangement of the Conflict of Interest is already provided for in Article 99of the Company Law, but did not explain the forms of Conflict of Interest by the directorand when a director can commit a transaction that causes the Conflict of Interest. Notspecifically about setting a standard conflict of interest standards and directorresponsibilities within the Company Law led to the decision maker can not do much tomake, weigh and impose sanctions on perpetrators of such conflicts of interest.